Gendered Fetishism and Emotional Capitalism in Digital Culture: Commodity, Care, and Control - Nissya Febrizani
The contemporary digital era marks a fundamental shift in the relationships between gender, affect, and economy. This study explores how emotional labor and gender identity are commodified within platform capitalism, focusing on the practices of female creators on Instagram, TikTok, and YouTube. Using digital ethnography and multimodal semiotic analysis, the study identifies three interrelated patterns. First, the monetization of vulnerability, where personal narratives—such as experiences with mental health or body image—are strategically leveraged to generate economic gains through sponsorships, affiliate links, and donation models. Second, the ritualization of care, which positions repetitive practices such as self-care routines as branding strategies, creating engineered intimacy and an aura of authenticity to maintain audience engagement. Third, algorithmic control, where platform infrastructures amplify affective content and shape creator behavior in alignment with attention-driven economic logic. These dynamics converge in what this study terms affective fetishism: the transformation of care, vulnerability, and authenticity into aestheticized commodities that appear natural but are systematically optimized for visibility and profitability. The digital performance of femininity is no longer mere self-expression; it is a curated product guided by algorithmic governance. This research contributes to discussions on emotional capitalism by demonstrating how gendered affect circulates as both symbolic and economic capital in digital culture. The findings highlight the ambivalent space between empowerment and exploitation, revealing how authenticity is not only a cultural value but also a commodified asset engineered for engagement in algorithmically mediated public spaces.